1997
DOI: 10.1007/bf02530049
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of non-invasive oscillometric maximum amplitude algorithm for estimating mean blood pressure

Abstract: A theoretical analysis is performed to evaluate the effect of arterial mechanical and blood pressure pulse properties on the accuracy of non-invasive oscillometric maximum amplitude algorithm (MAA) estimates of the mean blood pressure obtained using air-filled occlusive cuffs. Invasively recorded blood pressure pulses, selected for their varied shapes, are scaled to simulate a wide range of blood pulse pressures (diastolic blood pressure minus systolic blood pressure). Each scaled blood pressure pulse is trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(79 citation statements)
references
References 22 publications
0
77
0
1
Order By: Relevance
“…This discrepancy may be caused by the tendency of the oscillometric device to overestimate the blood pressure in conditions of decreased arterial wall distensibility. An overestimation of blood pressure in rigid or partly contracted arteries by the oscillometric method has been predicted by several theoretical studies (URSlNO and CRISTALLI, 1996;BAKER et al, 1997;RAAMAT et al, 1999). Results of computer simulations have shown that changes in vascular tone will lead to a shift of the maximum point of an oscillometric envelope.…”
Section: (A) Oscillometric Device Ut9201 and Finapres; (B) Diffbrenmentioning
confidence: 90%
“…This discrepancy may be caused by the tendency of the oscillometric device to overestimate the blood pressure in conditions of decreased arterial wall distensibility. An overestimation of blood pressure in rigid or partly contracted arteries by the oscillometric method has been predicted by several theoretical studies (URSlNO and CRISTALLI, 1996;BAKER et al, 1997;RAAMAT et al, 1999). Results of computer simulations have shown that changes in vascular tone will lead to a shift of the maximum point of an oscillometric envelope.…”
Section: (A) Oscillometric Device Ut9201 and Finapres; (B) Diffbrenmentioning
confidence: 90%
“…Although the mean values are different, the variances are too large. The correlation with the mean arterial pressure (MAP) [16,17] was investigated for each person separately. The equation resulting from the regression analysis is ASI = 0,039 · MAP + 2,2·10 -4 (2) and the p-value is 5,96·10 -9 .…”
Section: Ifmbe Proceedings Vol 51mentioning
confidence: 99%
“…P-V relationship is known to follow an exponential behaviour in the human circulation (Baker et al 1997, Burkhoff et al 2005 as noted in (1). Our assumption is that this practice is valid in the developed in vitro model which mimics the mechanics of the human circulation.…”
Section: Principlementioning
confidence: 99%